The Role of Firm Size and Sales Growth in Shaping Tax Avoidance Behavior - Bagja Baharudin; Merintan Berliana S (Annals of Justice and Humanity, 2026)
Purpose: This study examines the impact of credit effectiveness, third-party funds, and fee-based income on the financial performance of banking companies, measured by Return on Assets (ROA). The aim is to better understand how banking operational activities and income sources contribute to profitability and financial performance in the sector. Research Methodology: Using secondary data obtained from the Indonesia Stock Exchange during the 2020–2024 period, this study selected 30 banking companies using purposive sampling techniques. This study employed a quantitative approach using multiple linear regression analysis with the assistance of E-Views 9 software to examine the relationships among variables and determine their influence on financial performance. Results: The findings indicate that credit effectiveness, third-party funds, and fee-based income significantly influence the financial performance of banking companies. Partially, fee-based income demonstrates a significant positive effect on ROA, indicating that non-interest income plays an important role in enhancing bank profitability and operational efficiency. Conclusions: However, credit effectiveness and third-party funds show positive but statistically insignificant effects on financial performance, suggesting that these variables may require more optimal management to generate stronger profitability. Limitations: The study is limited to banking companies listed on the Indonesia Stock Exchange, and may not fully reflect banking conditions in other regions or periods. Additionally, secondary data may have reporting limitations or biases. Contributions: This study provides valuable insights for banking management, investors, and policymakers regarding the determinants of bank profitability and offers practical guidance for optimizing financial and operational strategies.